UPAYA PENINGKATAN KAPASITAS CELL 3G UNTUK MENGATASI MAX USER - ., Soeci Mahardika (Faculty of Engineering, Universitas Tanjungpura, 2017)
Abstrak- Increasing number of total consumer/users who communicate via telecommunications networks required a good capability of nodeB (3G BTS) in order to serve all users in the nodeB’s service area. When the number of customers served within a nodeB’s service area increased while the resource is less, it will increase the number of max user and decrease the service quality. So that requires increasing the nodeB’s capacity. Increasing the NodeB’s capacity can minimize the costs, it cheaper than build a new one. The nodeB that eligible to give a good service needs to reach KPI Standard such as accessibility above 98%, retainability above 99% and mobility above 95%. On 25 until 30 April 2016, there was increased number of user in NodeB Putussibau that caused the number of accessibility, retainability and mobility are below 90% based on KPI Standard. This causing many of users failed to make a call and also discomfort them when using the network. It is necessary to increase capacity, in this case is by using Nokia NetAct. After commissioning by using Nokia NetAct, there is a change of accessibility, retainability and mobility number in BTS Putussibau that all of parameters are above 99%. It can be concluded that user no longer experiencing disturbance when using the 3G network. Keyword : nodeB, capacity, NetAct Nokia, KPI standard